Blood urea nitrogen (BUN) in gastroenteritis with dehydration - Sjauli S. Amin; Jusniar B.; Suharjono Suharjono (Indonesian Pediatric Society, 1980)
The study on blood urea in 40 infants suffering from gastroenteritis and dehydration has been made with the following findings:Twenty two out of 40 cases (55%) showed blood urea content of more than40 mg%.Ten out of 40 cases (25%) still had blood urea content of more than 40mg % after rehydration.This high blood urea content after rehydration was more frequently found in neonates than in non-neonates infants (33.3% : 23.5%).